Sur/South : poetics and politics of thinking Latin America / India - Sur/South: Nuevos Pasajes a la India: América Latina/India (Conference) (2011 : Berlin, Germany); Klengel, Susanne; Ortiz Wallner, Alexandra (Madrid : Iberoamericana ; Frankfurt am Main : Vervuert, 2016)
"An awareness of the cultural entanglements in the Global South has become an evident as well as urgent factor in the global constitution of knowledge and the knowledges of globalization. This book contributes to the growing field of research on the relations between Latin America and Asia. From multiple perspectives and disciplinary backgrounds, it addresses the cultural and intellectual entanglements between Latin America and India in the 20th century. The Sur / South cultural cartography that emerges reveals the need for a new reflection on Orientalism as well."--P. [4] of cover.
A new poetics and politics of thinking Latin America, India. Sur, South and a different orientalism / Susanne Klengel, Alexandra Ortiz Wallner -- The Tagore-Ocampo Encounter : Tangled, Complex Realities : a personal research survey / Ketaki Kushari Dyson -- Cruces revolucionarios : la recepción de la poesía de Pablo Neruda en India / Vibha Maurya -- Analogy and convergence in Octavio Paz's the monkey grammarian or India as a source of liberation and reconciliation / Anthony Stanton -- Prosa del observatorio de Julio Cortázar como crítica epistemológica y manifiesto poético-politico : ¿una vislumbre budista? / Georg Wink -- The politics of orientalism and self-orientalism in a south-south dialogue : revisiting hispanic orientalism from said to sarduy / Julia A. Kushigian -- La Goa de Gilberto Freyre : Laboratorio lusotropical para el pensamiento transareal desde el Sur / Susanne Klengel -- Beyond the trans-atlantic matrix : Tagore and Latin America / Shyama Prasad Ganguly -- Narrativas de viaje a la India : Escritura del yo y género en el modernismo hispanoamericano / Alexandra Ortiz Wallner -- Alberto Masferrer : la influencia de la teosofía y de las corrientes hinduistas en las redes intelectuales centroamericanas (1890-1930) / Marta Elena Casaús Arzú -- Epistemología de la historia y estudios desde la subalternidad / Guillermo Zermeño Padilla -- Las voces desde el margen en la poesía afrocaribeña y en la de los dalits : una perspectiva comparada / Ashwani Kumar -- Apuntes en torno a los conceptos de postcolonialidad y subalternidad, su uso y significados entre los intelectuales de América Latina e India / Javier Pinedo -- De-territorializing experiences : translating between Indian and Brazilian postcolonial languages / Dilip Loundo -- Cinema as a cultural bridge between Brazil and India? : a comparative approach based on personal experience / Franthiesco Ballerini -- Postcoloniality in India and Latin America : neo-liberal modernity, urban dystopia and youth experience in cinema / Sonya Surabhi Gupta -- Las muchas encarnaciones de Tagore y los escritos de su espíritu / Cláudio Costa Pinheiro -- About the autors.
Incluye referencias bibliográficas.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2019. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Tagore, Rabindranath, -- 1861-1941 -- Influence -- Congresses; Tagore, Rabindranath, -- 1861-1941 -- Influencia -- Congresos; Indian literature -- Appreciation -- Latin America -- Congresses; Indian literature -- 20th century -- History and criticism -- Congresses; Latin American literature -- Appreciation -- India -- Congresses; Latin American literature -- 20th century -- History and criticism -- Congresses; Literatura india -- Apreciación -- América Latina -- Congresos; Literatura india -- Siglo XX -- Historia y crítica -- Congresos; Literatura latinoamericana -- Apreciación -- India -- Congresos; Literatura latinoamericana -- Siglo XX -- Historia y crítica -- Congresos; India -- Relations -- Latin America -- Congresses; Latin America -- Relations -- India -- Congresses; India -- Relaciones -- América Latina -- Congresos; América Latina -- Relaciones -- India -- Congresos; Libros electrónicos.